Effects of caffeic acid phenethyl ester on isoproterenol-induced myocardial infarction in rats - Oktar, Sueleyman; Aydin, Mehmet; Yonden, Zafer; Alcin, Erguel; Ilhan, Selcuk; Nacar, Ahmet (Aves, 2010)
Objective: Caffeic acid phenethyl ester (CAPE) is a natural product with potent anti-inflammatory, antitumor and antioxidant activities and attenuates inflammation and lipid peroxidation induced by ischemia-reperfusion injury. The purpose of the present study was to investigate the effects of CAPE on isoproterenol (ISO) -induced myocardial infarction. Methods: A randomized controlled experimental design was used in this study. Rats were divided into four groups and treated with saline, CAPE, ISO and ISO+CAPE. Rats were treated with CAPE (10 pmol kg/day i.p.) or saline starting 3 days before injecting ISO (150 mg /kg s.c., 24 hours). Seven days later, rats were sacrificed and the hearts were excised for biochemical analyses and microscopic examination. One-way ANOVA test with post hoc multiple comparisons using LSD method were used for statistical analysis of the data. Results: The administration of ISO alone resulted in higher myeloperoxidase (MPO) activity, lipid peroxidation, superoxide dismutase (SOD) and catalase (CAT) than in the control. The enzyme activities did not change in rat given CAPE alone. CAPE treatment prevented the increase in MPO activity and malondialdehyde, but did not affect the activities SOD and CAT enzymes. Conclusion: In light of these results, we conclude that CAPE prevents MPO-and lipid peroxidation-mediated myocardial injury via inhibition of neutrophil's MPO activity. (Anadolu Kardiyol Berg 2010; 10:298-302)
kafeik asit fenetil esterin siçanlarda isoproterenol indüklü miyokardiyal infarktüs üzerine etkileri
Keywords: Caffeic acid phenethyl ester; isoproterenol; myeloperoxidase; myocardial infarction; lipid peroxidation; oxidative stress